Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research. Issue 7 (3rd July 2022) - Ceban, Felicia; Leber, Alexia; Jawad, Muhammad Youshay; Yu, Mathew; Lui, Leanna M. W.; Subramaniapillai, Mehala; Di Vincenzo, Joshua D.; Gill, Hartej; Rodrigues, Nelson B.; Cao, Bing; Lee, Yena; Lin, Kangguang; et al.
Abstract: Background: A considerable proportion of individuals report persistent, debilitating and disparate symptoms despite resolution of acute COVID-19 infection (i.e. long COVID). Numerous registered clinical trials investigating treatment of long COVID are expected to be completed in 2021–2022. The aim of this review is to provide a scope of the candidate treatments for long COVID. A synthesis of ongoing long COVID clinical trials can inform methodologic approaches for future studies and identify key research vistas. Methods: Scoping searches were conducted on multiple national and international clinical trial registries. Interventional trials testing treatments for long COVID were selected. The search timeline was from database inception to 28 July 2021. Results: This scoping review included 59 clinical trial registration records from 22 countries with a total projected enrolment of 6718. Considerable heterogeneity was exhibited amongst component records with respect to the characterization of long COVID (i.e. name, symptoms- including frequency, intensity, trajectory and duration- mode of ascertainment, and definition of acute phase). In addition, the majority of proposed interventions were non-pharmacological and either targeted multiple long COVID symptoms simultaneously, or focussed on treatment of respiratory/pulmonary sequelae. Multiple interventions targeted inflammation, as well as tissue oxygenation and cellular recovery, and several interventions were repurposed from analogous conditions. Conclusions: The results of this scoping review investigating ongoing clinical trials testing candidate treatments for long COVID suggest that a greater degree of definitional stringency and homogeneity is needed insofar as the characterization of long COVID and inclusion/exclusion criteria.